In vitro gastrointestinal biotransformation and characterization of a Desmodium adscendens decoction: the first step in unravelling its behaviour in the human body. (12th July 2018) - van Dooren, Ines; Foubert, Kenn; Bijttebier, Sebastiaan; Breynaert, Annelies; Theunis, Mart; Exarchou, Vasiliki; Claeys, Magda; Hermans, Nina; Apers, Sandra; Pieters, Luc
Abstract: Objectives: The isolation and identification of the flavonoids present in a decoction of Desmodium adscendens was performed. In view of the oral use of the decoction, this work focused on the stability in gastrointestinal conditions and biotransformation by intestinal microflora in the colon of D-pinitol, vitexin and the flavonoid fraction of the decoction, as a first step in unravelling its behaviour in the human body. Methods: The freeze-dried decoction was first subjected to column chromatography. Subsequently an enriched flavonoid fraction, was separated by repeated semi-preparative high-performance liquid chromatography (HPLC) or by HPLC-SPE. The isolated compounds were elucidated by NMR. Biotransformation experiments were carried in an in vitro gastrointestinal dialysis model. Key findings: The major flavonoids of a decoction of D. adscendens were characterized as vicenin-2, isoschaftoside, schaftoside, 2″- O -xylosylvitexin, 2″- O -pentosyl- C -hexosyl apigenin and a O -hexosyl- C -hexosyl apigenin, tentatively identified as 2″- O -glucosyl-vitexin. During their passage in the gastrointestinal dialysis model, vitexin and C -glycosides thereof were found to be stable. Only the O -glycosidic bonds of O -glycosides of vitexin or isovitexin were hydrolysed during the colonic phase. Conclusions: A D. adscendens decoction was found to be rich in vitexin and isovitexin glycosides from which vitexin and the C -glycosides thereof were found to be stable in the simulated gastrointestinal tract.